Mir 135a inhibits tumor cell proliferation by regulating the expression of notch pathway in hepatoblastoma - Pu, Changsheng; Liu, Zhao; Chen, Jianfei; Wu, Tiantian; Zhang, Keming (Cellular and Molecular Biology, 2022)
MiRNA affects the proliferation, migration and cycle of tumor cells. However, the mechanism of regulating Notch pathway expression and inhibiting tumor cell proliferation in hepatoblastoma is not clear, we need to further explore. In this study, the dact2 gene can inhibit liver fibrosis. In this experiment, we used in vitro culture of hepatoblastoma cells and flow cytometry to detect the effect of miRNA-135a on the tumor cell cycle. The expression of miRNA-135a was detected by real-time PCR in 6 tumor samples and normal controls to observe and analyze the expression level of the important signal pathway proteins in the cells after mir-135a transfection. The cells were divided into the experimental group and the control group. The experimental group was transfected with miRNA-135a cells, while the control group was not transfected. Finally, the data are analyzed and discussed. from the third day, the activity of M17 cells in the mir-135a group began to be inhibited. By the fifth day, the inhibition rate of M17 was 50.64% (P < 0.01), and M21 was 25.02% (P < 0.01). In the experimental group, 53.38% of the cells were in the G1 phase, and mir-135a could block the tumor cells in G1 phase, affect the cell cycle process, and then affect cell proliferation.